Pengaruh Penguasaan Literasi Digital, Kompetensi Wirausaha dan Pendidikan Kewirausahaan terhadap Minat Berwirausaha pada Mahasiswa Universitas Muhammadiyah Jember - Safira, Yunita Filda Dewi; Izzuddin, Ahmad; Rusdiyanto Rusdiyanto (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to examine and analyze the influence of Digital Literacy Proficiency, Entrepreneurial Competence, and Entrepreneurship Education on Entrepreneurial Interest among students at Muhammadiyah University of Jember. This study focuses on identifying students' interest in entrepreneurship. A quantitative approach was used, employing regression analysis to test the relationship between independent variables (Digital Literacy Proficiency, Entrepreneurial Competence, and Entrepreneurship Education) and the dependent variable (Interest in Entrepreneurship). Students at Muhammadiyah University of Jember were selected as the research subjects because they align with the research problem. Data was collected through a questionnaire (Google Form) administered to students at Muhammadiyah University of Jember and will be analyzed using SPSS version 25. The results of the study indicate that Digital Literacy Proficiency positively and significantly influences students' entrepreneurial interest with a calculated t-value of 19.417, which is greater than the t-table value of 1.966 and a significance level of 0.000, which is less than 0.05. Entrepreneurial Competence also has a positive and significant effect on students' Entrepreneurial Interest with a t-value of 14.828, which is greater than the critical t-value of 1.966 and a significance level of 0.000, which is less than 0.05. Entrepreneurship Education also has a positive and significant influence on students' entrepreneurial interest, with a calculated t-value of 14.274, which is greater than the critical t-value of 1.966 and a significance level of 0.000, which is less than 0.05.